Association of TREM-1, IL-1β, IL-33/ST2, and TLR Expressions With the Pathogenesis of Ocular Toxoplasmosis in Mouse Models on Different Genetic Backgrounds - Zhang, Yanxia; He, Jian; Zheng, Huanqin; Huang, Shiguang; Lu, Fangli (Frontiers in Microbiology, 2019)
Ocular toxoplasmosis (OT) is one of the most common causes of posterior uveitis. The signaling of triggering receptor expressed on myeloid cells (TREM)-1 amplifies inflammation, whereas TREM-2 signaling is anti-inflammatory. IL-1β is a major driver of inflammation during infection. Toll-like receptors (TLRs) play important roles in protective immune response during Toxoplasma gondii infection, and interluekin (IL)-33 receptor (T1/ST2) signaling prevents toxoplasmic encephalitis in mice. However, the pathogenic mechanisms of OT are not yet well elucidated. To investigate the role of TREM-1, TREM-2, IL-1β, IL-33/ST2, and TLRs in OT of susceptible C57BL/6 (B6) and resistant BALB/c mice, both strains of mice were intravitreally infected with 500 tachyzoites of the RH strain of T. gondii. Histopathological analysis showed that T. gondii-infected B6 mice had more severe ocular damage observed by light microscopy, higher number of neutrophil elastase-positive cells in the eyes detected by immunohistochemical staining, more T. gondii tachyzoites in the eyes observed by transmission electron microscopy, and higher mRNA expression levels of tachyzoite-specific surface antigen 1 detected by quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) in comparison of T. gondii-infected BALB/c mice. Detected by using qRT-PCR, the mRNA expression levels of TREM-1, IL-1β, IL-33, ST2, TLR11, TLR12, and TLR13 were significantly higher in the eyes of T. gondii-infected B6 mice than those of T. gondii-infected BALB/c mice, whereas the mRNA expression levels of TLR3 and TLR9 were significantly higher in the eyes of T. gondii-infected BALB/c mice than those of T. gondii-infected B6 mice. Correlation analysis showed that significant positive correlations existed between TREM-1 and IL-1β/IL-33/ST2/TLR9/TLR11 in the eyes of B6 mice and existed between TREM-1 and IL-33/ST2/TLR3/TLR9/TLR13 in the eyes of BALB/c mice after ocular T. gondii infection. Our data revealed that, compared with T. gondii-resistant BALB/c mice, ocular T. gondii infection can stimulate higher production of TREM-1, IL-33, ST2, TLR11, TLR12, and TLR13 in the eyes of T. gondii-susceptible B6 mice, however, whether those lead to more severe ocular pathology in the susceptible B6 mice remain to be further studied.